Viscosity of Apis mellifera honey from different floral origins - SANTOMAURO, Rafael Alves; MANCUSO, Paula Santolin; ALMEIDA, Augusto Heitor Pedro de; CÉZAR, Camila Koutsodontis Cerqueira; CARON, Evelyn Fernanda Flores; SAMPAIO, Aryele Nunes da Cruz Encide; POSSEBON, Fabio Sossai; PEREIRA, Juliano Gonçalves; MARTINS, Otávio Augusto (Food Science and Technology, 2025)
Viscosity is a critical parameter that quantifies the flow rate of a liquid under an applied force, influenced by various factors including chemical composition, temperature, and humidity. This rheological property is particularly significant in the honey industry as it plays a crucial role in the design and optimization of processing equipment. The primary aim of this study was to characterize the viscosity of honey produced by Apis mellifera, sourced from various botanical origins, including organic varieties. The floral sources of the honey samples analyzed comprised eucalyptus (n = 8), wildflower (n = 8), orange blossom (n = 7), and organic production (n = 8). The results revealed that honey derived from orange blossoms exhibited the lowest viscosity, measured at 1,385.07 mm²/s, while organic honey displayed the highest viscosity, recorded at 4,344.78 mm²/s. Furthermore, organic honey demonstrated the highest concentration of hydroxymethylfurfural (33.59 mg/kg) alongside the lowest moisture content (18.20%). These findings suggest that the lower moisture content and varied chemical composition of honey contribute to enhanced crystallization processes, resulting in increased viscosity.